Bank lending in Switzerland: Capturing cross-sectional heterogeneity and asymmetry over time - Toni Beutler; Matthias Gubler; Simona Hauri; Sylvia Kaufmann (Swiss National Bank, Study Center Gerzensee, 2020)
We study the bank lending channel in Switzerland over three decades using unbalanced quarterly bank-individual data spanning 1987 to 2016. In contrast to the usual empirical approach, we take an agnostic stance on which bank characteristic drives the heterogenous lending response to interest rate changes. In addition, our empirical model allows for a changing lending reaction occurring over time in a state-dependent manner. Our results are consistent with the existence of a bank lending channel, which is however muted in specific periods. Such episodes are characterized by increased economic uncertainty, which negatively impacts loan growth.
Keywords: C11; C34; E44; E52; G21; 330; Bank lending channel; economic uncertainty; Markov switching model; Bayesian econometrics; unbalanced panel